A framework to foster accessibility in post-pandemic virtual higher education - Ricardo Mendoza-González; Cristian Timbi-Sisalima; Mary Sánchez-Gordón; Salvador Otón-Tortosa (Heliyon, 2024)
The SARS-CoV-2 Coronavirus pandemic (COVID-19) forced educational institutions to move their programmes to the virtual world. Several tech-based solutions –including virtual training and tutoring, discussion forums, access to content and information, collaborative platforms, and Open Educational Resources (OER)– were implemented to address this shift and continue to be used in the post-pandemic era due to the advantages they offer, especially for hybrid and blended learning. However, the implementation of these tech-based solutions also revealed several accessibility issues that need to be addressed to fully leverage the technological benefits. This study aims to provide a framework to facilitate the adoption of good practices related to technological accessibility in virtual Higher Education. The implementation of the framework is divided into four basic actions, each of which should be tailored to the constraints and needs for improving accessibility in Higher Education Institutions (HEIs). The framework's instantiation in four HEIs serves as a proof-of-concept in real-world scenarios. The preliminary results suggest that the proposal is promising, as it was adaptable to the specific needs of each HEI fostering accessibility and inclusion through technological alternatives that align with their organisational structures and current levels of attention to accessibility.